A phenomenological study of differentiated instruction experience in an Ethiopian middle school: The case of grade 7 students in Hawssa city, Ethiopia - Fozia Temam Mohammed; Taye Gebremariam Olamo; Mesfin Abera Yemiru (PLoS ONE, 2026)
This phenomenological study investigates middle school students’ and their English language teacher’s experience with differentiated instruction in a writing classroom. The aim was delving into the lived experiences of the students and the teacher to uncover insights as well as benefits and challenges encountered in writing instruction. The study was conducted at Stadium Elementary School in the city of Hawassa, Ethiopia. A total of 32 middle level students aged 13/14 and their English language teacher were participants of the study. Of these, six students and the teacher were subjects for the interview. Data were gathered through face-to-face interviews and observation of a classroom. Data was analyzed thematically. The findings of the study revealed that differentiated instruction provided students with tailored support, leading to enhanced motivation, engagement, and confidence in their writing abilities. As a challenge some students’ unfamiliarity and resistance to the approach emerged Moreover, the teacher’s experience revealed the demanding nature of the approach and need of collaboration from stakeholders. We conclude that, when the concerns raised by research participants are effectively addressed, the incorporation of differentiated instruction has strong potential to improve students’ writing outcomes and engagement, offering a practical approach for educators seeking to personalize learning and enhance writing quality.